KAPASITAS PEMERINTAH DALAM PEMBANGUNAN INFRASTRUKTUR BERSUMBER DANA DESA DI KAMPUNG RAWANG KAO KECAMTAN LUBUK DALAM KABUPATEN SIAK TAHUN 2018 - Taupiq Gandhi Mahatma; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Capacity is the ability, skills, understanding, attitudes, values, relationships, behavior, motivation, resources and conditions that enable individuals, organizations, networks / sectors, and the broader system to carry out their functions and achieve the development goals that have been set from time to time. In order to increase the professionalism of the village government, it is necessary to pay attention to: the development of the capacity of the village government with the priority of increasing the capacity in public services such as basic community needs, security and ability to deal with disasters, the ability to prepare strategic plans for village economic development, the capacity for village financial management, and sustainable management. environment.This study aims to understand the Government's Capacity in Developing Village Fund-Sourced Infrastructure in Rawang Kao Village, Lubuk Dalam District, Siak Regency in 2018. The research was conducted in Rawang Kao Village, Lubuk Dalam District, Siak Regency. This data collection technique is done by interview and documentation. The method used in this research is descriptive qualitative.The results of this study indicate that the capacity of the village government in infrastructure development based on village funds can be measured through Morgan's theory in Soeprapto, namely, abilities, skills, understanding, attitudes, values, relationships, behavior, motivation, resources and conditions that allow individuals, organizations, networks and systems to more broadly carry out functions. The research conducted can conclude that the capacity of the village government in developing infrastructure sourced from village funds is still not running well in its implementation, there are still many village government officials who do not understand the tasks and functions that have been given. It is felt that the training that should be carried out continuously by the central government plays an important role in increasing the capacity of village government officials. The ability of the village apparatus greatly influences the performance that will be given, thus human resources should be properly selected again so that the village government works optimally and gives optimal results.Keywords: Capacity, Infrastructure Development, Village Fund